PERAN RELIGIOUS COPING DAN SENSE OF COMMUNITY TERHADAP PSYCHOLOGICAL WELL-BEING JEMAAT DI GEREJA X - Gavriella Ceacilia Christie Ratu Edo (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Psychological well-being is an important aspect for church congregations in living their lives. However, research examining the simultaneous role of religious and social factors on the psychological well-being of congregations is still limited. This study aims to analyze the role of religious coping and sense of community on the psychological well-being of congregations at Church X. This study uses a quantitative approach involving 112 congregants of Church X as research subjects. Data were collected using scales of religious coping, sense of community, and psychological well-being, then analyzed using multiple linear regression. The results show that negative religious coping plays a significant role in reducing the psychological well-being of congregants, while positive religious coping does not play a significant role. Sense of community also did not show a significant role in the regression model. These findings indicate that the quality of religious experience, particularly in the form of negative religious coping, has a more meaningful influence on psychological well-being than the intensity or socio-religious aspects measured in this study. In addition, the results of this study indicate that the psychological well-being of congregations is likely influenced by other psychological factors beyond the variables studied. ABSTRAKPsychological well-being merupakan aspek penting bagi jemaat gereja dalam menjalani kehidupan. Namun, penelitian yang mengkaji peran faktor religius dan sosial secara simultan terhadap psychological well-being jemaat masih terbatas. Penelitian ini bertujuan untuk menganalisis peran religious coping dan sense of community terhadap psychological well-being jemaat di Gereja X. Penelitian ini menggunakan pendekatan kuantitatif dengan melibatkan 112 jemaat Gereja X sebagai subjek penelitian. Data dikumpulkan menggunakan skala religious coping, sense of community, dan psychological well-being, kemudian dianalisis dengan regresi linear berganda. Hasil penelitian menunjukkan bahwa negative religious coping berperan signifikan dalam menurunkan psychological well-being jemaat, sedangkan positive religious coping tidak menunjukkan peran yang signifikan. Sense of community juga tidak menunjukkan peran yang signifikan dalam model regresi. Temuan ini mengindikasikan bahwa kualitas pengalaman religius, khususnya dalam bentuk coping religius yang negatif, memiliki pengaruh yang lebih bermakna terhadap psychological well-being dibandingkan intensitas atau aspek sosial-keagamaan yang diukur dalam penelitian ini. Selain itu, hasil penelitian ini menunjukkan bahwa psychological well-being jemaat kemungkinan dipengaruhi oleh faktor psikologis lain di luar variabel yang diteliti.